Potentially synbiotic product based on Andean blackberry (Rubus glaucus) by applying vacuum impregnation - Rodríguez-Barona, Sneyder (2012)
The aim of this study was to develop a product potentially symbiotic by applying vacuum impregnating over Andean blackberry slices immersed in three solutions: a solution of fructooligosaccharides (FOS), natural blackberry juice, and a mixture of fruit juice and solution of FOS, inoculated with Lactobacillus casei ATCC 393 with 109 UCF/mL. The blackberry slices impregnated with the mixture of fruit juice and FOS, and with just the FOS solution, they were found to contain 108 UCF/g and over 0.0022 g of FOS per 100g of impregnated sample after being stored for 72 hours under refrigeration conditions. The results indicate that the presence of FOS in the impregnation solution increases the viability of the microorganisms and it can be concluded that it is feasible to obtain a potentially symbiotic food from Andean blackberry by means of the impregnation of its porous matrix with beneficial microorganisms and prebiotic substances.